(3GdJPcQI aj GdbQGAGJs - (3CHh GdMSf WGgQ Hf YHO GdefYe Hf YHjO Gddg Hf ZdHhf GdebQj,J (B380 (3g` s
(3ChdgG (B:s
(3bGd CHh GdMSf WGgQ Hf YHO GdefYe Hf ZdHhf GdebQi aEfi PGcQ ai gPG GdcJGH ef bQGAI CFeI GdCeUGQ GdeTghQjf HGdEHMGQ JPcQI ddYGde HGH PcQ GdCSGfjO GdJi fbdJ EdjfG gPg GdbQGAI s
(3BNQgG (B:s
(3JSbW Cda GdhUd GdJi ai Chd bhdc Gddg CcHQ CjVkG ddESJZfGA YfgG bGdMeO Ydi eG QSeJ dc fUH GdUhGH hJQTO Ef TGA Gddg YR hLd Je GdcJGH HMeO Gddg hefg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B392s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdbQGAGJ hGdJLhjOs